UPAYA MENINGKATKAN HASIL BELAJAR EKONOMI MELALUI PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TGT (Teams Games Tournament) - Eva Jhulliana, ; Tri Mugiarti, (Pendidikan Ekonomi, 2012)
The purpose of this study is to find out the teacher and students activities and to find out the learning outcome. This study applies the class action research (PTK), the research subject is the X-3 Senior high school state I Waru Sidoarjo. This study found that the teachers activities is very good with the escalation in each cycle (64,7% and 83,8%), and the students activities also very good with the growth percentages in each cycle (65% and 82,5%). The students learning outcome also increases in its classical completeness 61% to 83,33% by employing the cooperative type TGT (Teams Games Tournament) learning model.